Compatibility, compossibility, and epistemic modality - Holliday, Wesley H.; Mandelkern, Matthew (Proceedings of the Amsterdam Colloquium, 2025)
We give a theory of epistemic modals in the framework of possibility semantics and axiomatize the corresponding logic, arguing that it aptly characterizes the ways in which reasoning with epistemic modals does, and does not, diverge from classical modal logic.